Blockchain Implementation on Subsidised LPG Distribution in Gas Supply Chain (Case Study: Medan) - Habibie Satrio Nugroho (Talenta Publisher, 2025)
This study examines the potential of private blockchain technology on the Multichain platform for the implementation of a subsidised gas distribution information system in Medan. The objective is to enhance transparency, security, and reliability. The data were collected via a literature review and documentation analysis, and the system was developed using the waterfall methodology. The Multichain-based architecture ensures secure, transparent, and traceable transactions, thereby reducing the incidence of fraud and discrepancies. The results demonstrate that the architecture fulfils the requisite criteria, establishing a robust framework for gas distribution. This validates the effectiveness of Multichain-based private blockchain for improved efficiency and reliability in Medan's subsidised gas distribution system.